Platform for Improving the User Experience in the Creation of Educational Multiplayer Video Games - Sánchez-Canella, Fernando; Pascual-Espada, Jordán; Cid-Rico, Irene (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2024)
Students’ motivation is one of the factors that directly affect academic performance. In recent years, teachers are looking for ways to motivate students during their training period. For example, making use of slides, videos, films, comics or games to increase students' motivation to improve their learning experience. Some research works have revealed that multiplayer games which include cooperation and competition, among other factors, are an extraordinary tool for enhancing students’ motivation. Current alternatives make it very complex for teachers to create multiplayer games for their students. The definition of the game requires many configurations and even technical knowledge. This research proposes a new platform that allows teachers to create multiplayer video games in a simple and fast way, improving the game creation process over current alternatives. The resulting games are also designed for to improve the student experience, and make it fun. These games do not only include trivia questions, but also use functional mechanisms from video games. The design of the generated games allows students to master the games in a short period of time during their classes
Keywords: e-learning; gamification; multimedia; usability; videogame